Pengaruh Pendidikan dan Kesehatan terhadap Produktivitas tenaga Kerja di Provinsi Jambi tahun 2002-2020 - Sylvia Novista (Universitas Batanghari Jambi, 2021)
The problem that always arises in societal life is poverty. Various efforts made by the Government to reduce poverty reduce poverty can not be done partially but should concern some aspects related to poverty. This research aims to analyze the factors that affect poverty in Jambi city in 2003-2017. The factors analyzed are economic growth rate, unemployment, HDI and poverty in Jambi city. The data used in this research is sourced from the Central Statistic Agency (BPS) which has a record of data from 11 regencies/cities in Jambi province. The method used in this research is a method of double linear regression using SPSS method with research time of 2003-2017. The results of this study showed that of the 3 variables tested, the economic growth rate was influential Significant impact on poverty, human Development index has no significant effect on poverty. While unemployment significantly positively affects poverty. The result of this study is LPE, IPM, UN, had a significant impact on the poverty rate of the Jambi city. It was with the amount of coefficient determination 47,30% the rest 52,7% was influenced by more variables than research.